Dendritic cell engineering for tumor immunotherapy: from biology to clinical translation. (July 2012) - Bhargava, Arpit; Mishra, Dinesh; Banerjee, Smita; Mishra, Pradyumna Kumar
Dendritic cells (DCs) are the most potent APCs, with the ability to orchestrate a repertoire of immune responses. DCs play a pivotal role in the initiation, programming and regulation of tumor-specific immune responses, as they are poised to take up, process and present tumor antigens to naive or effector T lymphocytes. Although, to an extent, DC-based immunotherapeutic strategies have successfully induced specific anti-tumor responses in animal models, their clinical efficacy has rarely been translated into the clinic. This article attempts to present a complete picture of recent developments of DC-based therapeutic strategies addressing multiple components of tumor immunoenvironment. It also showcases certain practical intricacies in order to explore novel strategies for providing new impetus to DC-based cancer vaccination.